MOTOR ABILITIES OF FEMALE STUDENTS WITH REGARD TO THEIR WORK CONDITIONS - Viktor Mitrevski; Georgi Georgiev; Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The research is conducted on a samples of 183 female entities at high school. The sample is divided into 3 sub-samples according to the work conditions at school. Eight (8) motor test are applied in order to establish the possible differences between the subsamples; and the conclusion is that, in four (4) out of the eight (8) tests within analysis of variance (ANOVA) and multivariate analysis of variance (MANOVA), there is a statistically significant difference between the treated groups.